Development of an inactivated candidate vaccine against Chandipura virus (Rhabdoviridae: Vesiculovirus) - Jadi, R.S. (Vaccine, 2011)
A Vero cell based vaccine candidate against Chandipura (CHP) virus (Rhabdoviridae: Vesiculovirus), was developed and evaluated for immunogenicity in mice. Virus was purified by ultracentrifugation on 30% glycerol cushion followed by differential centrifugation on 10–60% sucrose gradient and inactivated with β-propio lactone at a concentration of 1:3500. The inactivated product was blended with aluminium phosphate (3%) and immunized 4-week-old Swiss albino mice. Neutralizing antibodies in the range of 1:10 to 160 and 1:80 to 1:320 was detected with 85% and 100% sero-conversion after 2nd and 3rd dose, respectively. All the immunized mice with antibody titer above 1:20 survived live virus challenge. The vaccine candidate has potential to be an efficient vaccine against CHP virus.